Capital and Ownership Structures, and the Market for Corporate Control - Israel, Ronen (Review of Financial Studies, 1992)
The author analyzes optimal capital and ownership structures as resulting from anticipated future control contests. He focuses on leverage as a device that enables the incumbent management to extract the maximum value from the rival. He shows that firm value depends on both capital and ownership structures. The analysis leads to the following predictions: (1) more efficient managers use less debt, (2) firms facing better rivals for control issue more debt, and (3) firms with supermajority rules issue less debt. Several predictions are consistent with known empirical regularities. Article published by Oxford University Press on behalf of the Society for Financial Studies in its journal, The Review of Financial Studies.